2019
DOI: 10.1016/j.celrep.2019.01.113
|View full text |Cite
|
Sign up to set email alerts
|

Communication between the Anterior Cingulate Cortex and Ventral Tegmental Area during a Cost-Benefit Reversal Task

Abstract: Graphical Abstract Highlights d Anticipatory decision making is associated with increased ACC/VTA signaling d Sustaining behavior toward a new default is associated with ACC/VTA signaling d Error-related feedback integration is associated with increased VTA/ACC signaling d Error-related VTA/ACC signaling is predictive of subsequent choice adaptation Correspondence telston@nurhopsi.org In Brief Elston et al. find that the initiation and persistence of non-default behavior are associated with increases in top-do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 59 publications
(95 reference statements)
0
11
0
Order By: Relevance
“…ACC is known to receive VGluT1 inputs from the Claustrum (CLA) and Hippocampus (Chia et al, 2020;Kol et al, 2020;Qadir et al, 2018;White et al, 2018). Moreover, it also receives a plethora of neuromodulatory inputs from the Ventral Tegmental Area (VTA) and the Raphe nuclei (Sun et al, 2019;Elston et al, 2019). In the future, investigation of the ACC-DMS neurons and their functional connectivity will expand our knowledge of this critical circuit required for effort/reward evaluation and adaptability of instrumental actions.…”
Section: Excitation Of Acc-dms Circuit Reduces Effort Exertionmentioning
confidence: 99%
“…ACC is known to receive VGluT1 inputs from the Claustrum (CLA) and Hippocampus (Chia et al, 2020;Kol et al, 2020;Qadir et al, 2018;White et al, 2018). Moreover, it also receives a plethora of neuromodulatory inputs from the Ventral Tegmental Area (VTA) and the Raphe nuclei (Sun et al, 2019;Elston et al, 2019). In the future, investigation of the ACC-DMS neurons and their functional connectivity will expand our knowledge of this critical circuit required for effort/reward evaluation and adaptability of instrumental actions.…”
Section: Excitation Of Acc-dms Circuit Reduces Effort Exertionmentioning
confidence: 99%
“…For example, the VTA entrains both areas during working memory (Fujisawa and Buzsá ki, 2011) and could do the same during remote recall. However, it is worth mentioning that the ACC can also drive VTA activity during high-effort responses (Elston and Bilkey, 2017;Elston et al, 2019), and one could argue that remote recall is a high-effort cognitive process. All these possibilities require further experimentation to evaluate, but given the data presented here, the simplest explanation is that the ACC is driving CA1 activity via theta oscillations during remote recall.…”
Section: Acc Effects On Hc Functionmentioning
confidence: 99%
“…However, it is now known that the involvement of the dopaminergic system in the reward encoding process does not mean that this system gives animals pleasurable feelings [18][19][20]. Later research has suggested that, apart from dopaminergic system, other brain areas such as the anterior cingulate cortex (ACC), prefrontal cortex, and limbic systems, etc., are also involved in the encoding of rewards for the decision-making process [21][22][23][24]. Finding multiple brain regions that could encode the reward does not imply the failure of seeking a congruent pattern with incongruent results.…”
Section: Reward Encoding and Learningmentioning
confidence: 99%
“…For those neurons with activity that is correlated with the predicted task value, a pattern can be seen as to whether the value is modulated by probability or reward size [24]. Interestingly, the connections between the VTA and ACC appear to be important outcome learning and action execution, with the ACC-to-VTA signalling being involved in anticipatory choice and the VTA-to-ACC signalling being involved in error detection [23]. This is consistent with the idea that ACC is a site for action selection for the acquisition of rewards.…”
Section: Other Brain Areas and Model-based Choicesmentioning
confidence: 99%